Fatty acid content obtained from the guinea pig meat (2015)
The study´s aim was to determine the fatty acid composition from the guinea pig meat. The study was conducted in the Riobamba City, Ecuador. The guinea pigs lines used were: Creole, Andean and Improved Peruvian. Itwas carried out a variance analysis forthe differences and measurements comparison according Duncan (P < 0.05). The total content of saturated fatty acids in this rodent meat did not registered statistical differences between the lines studied, with values of 37,1 1, 37,01 and 36,71 % for the guinea pigs Creole, Andean and improved Peruvian respectively.Neither the content of monounsaturated acids reported statistical differences between the three lines, as they showed levels of 30.49, 29.26 and 31.44% respectively for Creole, Andean and Peruvian lmproved lines, with no statistical differences.Levels of polyunsaturated fatty acids in the meat of this rodent were 13,30, 11,04 and 14,22% in Creole, Andean and Peruvian improved, having no statistical difference between them.